1-Carb-oxy-methyl-3-octylimidazolium bromide - Al-Mohammed, N.N.; Alias, Y.; Abdullah, Z.; Khaledi, H. (International Union of Crystallography, 2011)
In the title compound, C(13)H(23)N(2)O(2) (+)·Br(-), the octyl chain has an all-trans conformation. In the crystal, the cations are linked by C-H⋯O bonds into a zigzag chain along the b axis. The bromide anions further link the chains via C-H⋯Br inter-actions into a two-dimensional array parallel to the ab plane. An O-H⋯Br interaction is also observed.